2020
DOI: 10.3390/nano10081517
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Preparation of Carbon Nanotubes from Waste Polyethylene Using FeNi Bimetallic Nanocatalyst

Abstract: In this work, carbon nanotubes (CNTs) were synthesized by catalytic pyrolysis from waste polyethylene in Ar using an in-situ catalyst derived from ferric nitrate and nickel nitrate precursors. The influence factors (such as temperature, catalyst content and Fe/Ni molar ratio) on the formation of CNTs were investigated. The results showed that with the temperature increasing from 773 to 1073 K, the carbon yield gradually increased whereas the aspect (length-diameter) ratio of CNTs initially increased and then d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…[108][109][110][111] When Ni, Fe, and NiÀ Fe alloy nanoparticles are used to convert plastics, carbon nanotubes or carbon nanofibers are commonly obtained. [89,[96][97][98] Metal-support interaction has exerted great effects on carbon formation. A study on alumina-supported Ni, Fe, Co, and Cu catalysts in the carbonization of low-density PE demonstrated that carbon nanotubes were successfully generated on Ni, Fe, and Co but were barely obtained on Cu catalyst.…”
Section: Thermocatalysismentioning
confidence: 99%
See 2 more Smart Citations
“…[108][109][110][111] When Ni, Fe, and NiÀ Fe alloy nanoparticles are used to convert plastics, carbon nanotubes or carbon nanofibers are commonly obtained. [89,[96][97][98] Metal-support interaction has exerted great effects on carbon formation. A study on alumina-supported Ni, Fe, Co, and Cu catalysts in the carbonization of low-density PE demonstrated that carbon nanotubes were successfully generated on Ni, Fe, and Co but were barely obtained on Cu catalyst.…”
Section: Thermocatalysismentioning
confidence: 99%
“…Most plastics including PE, PP, PS, and PET are mainly composed of carbon and hydrogen elements, and consequently they can serve as ideal resources for the production of value‐added carbon materials and hydrogen gas. Over the past years there has been substantial interest and research into the conversion of plastics into various carbon materials, in particular, carbon nanotubes, carbon nanofiber, graphene, and so on [79–99] . Though these carbon materials have varied morphology and structure, the synthesis procedures for them share two key steps: the degradation of plastics into small carbonaceous molecules and their subsequent carbonization.…”
Section: Carbon Materials and Hydrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al synthesized CNTs from the polyethylene waste, and diameter and length was 20-30 nm and few tens of micrometers, respectively. Used as a field of composite materials were solar cells and optical devices [77]. Singh et al synthesized CNTs from industrial waste, namely, fly ash, red mud, and rock sample, and used for the removal of methyl orange from aqueous medium.…”
Section: Industrial Waste As a Source Of Cntsmentioning
confidence: 99%
“…It can also be utilized to handle plastic trash from various novel materials, including composites, particularly during the early phases of development when market volumes of new materials are restricted and separate garbage collection is not a viable alternative [7]. In addition, by adjusting reactor types, reaction temperatures, and types of catalyst, the pyrolysis process allows the product to be fine-tuned [8][9][10]. This is highly beneficial in terms of the whole economic cycle.…”
Section: Introductionmentioning
confidence: 99%